SCARLETT O’HARA, SOLOMON NORTHRUP, AND TA-NEHISI COATES: HELPING STUDENTS GRASP THE RELATIONSHIP BETWEEN POPULAR CULTURE AND CONTEMPORARY RACIAL POLITICS - Rank, Allison D. (Dialogue, 6(1), 2019)
The post-racial perspective of many millennial college students can make it challenging for faculty to engage students in serious conversations about race in America and the relationships among popular culture, political culture, and race-conscious policies. This article outlines a three-week unit from a course entitled Popular Culture and Politics that uses Gone with the Wind (1939) and 12 Years a Slave (2013) along with academic and popular articles to walk students through three interconnected concepts: (1) the conflicting images of slavery as a system in American political history; (2) the role of popular culture in constructing and disseminating those images; and (3) the connections between the cultural understanding of America’s racial history and the contemporary political landscape. This piece provides an overview of the objectives of each section of the unit, including summaries of readings, sample discussion questions, and a summative assignment–all of which can be adapted for a variety of disciplines. Keywords: Political Culture, Ideology, Reparations, Gone with the Wind, 12 Years a Slave
Keywords: Type of access: Open Access